REVITALIZATION OF HIGHER EDUCATION FOR SOCIO-ECONOMIC EMANCIPATION IN NIGERIA - Aselebe, Kamorudeen Oladapo (African Journal of Educational Management, 2022)
Socio-economic development is the primary goal of every well-meaning government, and it is essentially dependent on the level of economic activities in a country. There is no doubt about the fact that Nigeria socio-economic activities is confronted with daunting challenges and this includes poverty, insecurity, high rate of unemployment, banditry, low industrial output, unstable and deteriorating exchange rate, high inflation rate, inadequate physical and social infrastructure, very large domestic debt, and rising stock of external debt among others. Socio-economic emancipation relies on quality of human capital resource and this is a product of higher education in Nigeria. The contribution of Nigerian higher education is crucial if the country is to witness an increase in socio economic emancipation. Regrettably, a close look at the Nigerian higher education reveals that it is confronted with myriads of problems, which made it impossible to achieve the goal of contributing to socio-economic development of the country. This paper suggested ways of revitalizing higher education for socio economic emancipation in Nigeria. Suggestions raised include that government should ensure larger percentage of her budget is allocated for higher education, while every stakeholder should rise up to fund higher education so as to achieve socio-economic emancipation in Nigeria. Also, higher institutions should put in place strategic plan for impacting employability skills in their students, so as to prepare them for the tasks of life after schooling.